Optimization of three-bed VPSA system for biogas upgrading - Yin, Chunbiao; Sun, Weina; Yang, Huawei; Zhang, Donghui (Chemical engineering science, 2015)
An optimization for biogas upgrading process by three-bed 12-step vacuum pressure swing adsorption (VPSA) was performed in this work. The raw gas composed of 60% CH4 and 40% CO2 was used at 313.15K with the pressure of 101.325kPa. Co-current replacement with heavy component step and counter-current pressurization with replaced exhaust step were applied in the VPSA system. The results indicated that the adoption of these two steps actually helped enhance the CH4 recovery and the specific productivity of CH4. The objective pursued in this work was evaluated by the combination of the specific energy consumption, the CH4 recovery and the specific productivity of CH4. The effects of these decision variables on the objective were evaluated by the r-SQP algorithm. According to the optimization performed for a stream of biogas of 37Nm3/h, it was possible to obtain bio-methane with a purity of 98.00%, a recovery of 93.23% with a specific productivity of 0.1331Nm3/kg/h and a specific energy consumption of 0.3697kWh/kg of produced methane. •A three-bed 12-step VPSA process applied to upgrade biogas.•The r-SQP algorithm used to optimize the decision parameters of this process.•Improving the CH4 recovery and the unit productivity of CH4 while reducing the unit energy consumption.•An important improvement in the performance of the three-bed 12-step VPSA process.